Michael Riffaterre’s ‘Interpretant’ Reinterpreted - Krawczyk, Mateusz Andrzej (The Biblical Annals, 2020)
Bible exegesis is dealing at times with the accusation of superficial implementation of methods from various fields of science and of disrespect for the theological character of the Bible in hermeneutical and methodological presuppositions. This accusation can be directed also towards the many uses of intertextuality in biblical scholarship. The article challenges this situation and proposes what has been called a ‘theological model of intertextual interpretation’ – an approach based on literary theory of the ‘interpretant’ as understood by Michaele Riffaterre – that tends to respect more fully the theological character of the biblical text. After a detailed description of the approach and its methodological elements, the second part of the article deals with an example of the application of thereof – an intertextual exegesis of Rom 2:7 and Wis 2:23; Wis 6:18.19.